The Impact of Cardiac Diseases during Pregnancy on Severe Maternal Morbidity and Mortality in Brazil - Campanharo, Felipe F. (PLoS One, 2015)
BACKGROUND: To evaluate maternal heart disease as a cause or complicating factor for severe morbidity in the setting of the Brazilian Network for Surveillance of Severe Maternal Morbidity. METHODS AND FINDINGS: Secondary data analysis of this multicenter cross-sectional study was implemented in 27 referral obstetric units in Brazil. From July 2009 to June 2010, a prospective surveillance was conducted among all delivery hospitalizations to identify cases of severe maternal morbidity (SMM), including Potentially Life-Threatening Conditions (PLTC) and Maternal Near Miss (MNM), using the new criteria established by the WHO. The variables studied included: sociodemographic characteristics, clinical and obstetric history of the women; perinatal outcome and the occurrence of maternal outcomes (PLTC, MNM, MD) between groups of cardiac and non-cardiac patients. Only heart conditions with hemodynamic impact characterizing severity of maternal morbidity were considered. 9555 women were included in the Network with severe pregnancy-related complications: 770 maternal near miss cases and 140 maternal death cases. A total of 293 (3.6%) cases were related to heart disease and the condition was known before pregnancy in 82.6% of cases. Maternal near miss occurred in 15% of cardiac disease patients (most due to clinical-surgical causes, p<0.001) and 7.7% of non-cardiac patients (hemorrhagic and hypertensive causes, p<0.001). Maternal death occurred in 4.8% of cardiac patients and in 1.2% of non-cardiac patients, respectively. CONCLUSIONS: In this study, heart disease was significantly associated with a higher occurrence of severe maternal outcomes, including maternal death and maternal near miss, among women presenting with any severe maternal morbidity.